(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In recent times, carious infection of the tooth is considered as a major worldwide concern, significantly impacting the health, safety and quality of life of the patients affected by it. The required routine oral hygiene procedure along with fluoride use ensures prevention against dental caries. Apart from these, another important prophylactic measure can be followed against the caries by sealing the pit and fissures of a tooth that is more prone to caries occurrence. The main purpose of this article is to present a general overview of the sealing of pits and fissures, materials typically used to seal the occlusal surfaces along with the implications and side effects. This article also presents a detailed review of safe, effective use and costeffectiveness of pit and fissure sealants as a preventive measure for caries. The finding drawn from this is that primary, as well as permanent teeth, sealed pit and fissures are an efficient and appropriate approach for preventing and arresting dental caries. But conducting a proper regular dental check-up is necessary to ensure that there is no advanced tooth decay caused due to any leakage in the sealing.